AI-based assisting tool to accommodate special needs of students - Achwan, Kristian Hadinata (Nanyang Technological University, 2025)
Students with special needs in higher education often encounter multifaceted challenges that can undermine their academic success and overall well-being. Especially common, though frequently unrecognized, is Attention-Deficit/Hyperactivity Disorder (ADHD), which affects a significant proportion of university students. This underdiagnosis might lead to substantial disruptions in terms of time management, focus, and overall academic performance, as traditional teaching methods rarely account for the diverse cognitive needs of such students.